(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kushnir O. А. Skill formation of the correct situation awareness in the structure of professional reliability of flight crews. The paper outlines the rationale for the development and implementation of new pedagogical approaches to the training of future pilots – namely, learning the correct form of situation awareness. The concept of «situation awareness», its essence, the algorithm of formation and implications for professional reliability of crews is analyses.